Territorial development and border cities. A theoretical debate - Medeiros, E. (2022)
In the European Union, around 30% of the population live in border regions (border NUTE 3), covering approximately 40% of the territory. These regions have, for the most part, lower territorial development levels than non-border regions. The exceptions are commonly the border cities which serve as anchors of development for the entire border region, making their analysis especially important for better understanding the territorial development challenges, as well as the territorial capital and trends of border regions. In this context, this chapter presents a theoretical framework of the territorial development process while linking it to the potential contribution of border cities to the territorial development of border regions. The chapter concludes with the analysis of the territorial development trends of the main EU border cities during the last decade (2005-2015), largely based on statistical elements and available literature. Based on the European case, 65 border twin cities were identified and analysed. These are, with few exceptions, small and medium-sized cities, located in lagging regions. However, they hold the key to increase the territorial development potential of EU border regions, since they concentrate the human and socioeconomic capital of these regions.